AKTIVITAS INHIBISI α-GLUKOSIDASE PADA MINUMAN FUNGSIONAL JAHE (Zingiber officinale Roscoe) DENGAN PENAMBAHAN EKSTRAK KULIT MELINJO KUNING (Gnetum gnemon Linn.) - Tagor Marsillam Siregar; Aileen Neysha (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2020)
Yellow melinjo (Gnetum gnemon Linn.) peel extract contains active components such as resveratrol, tannin, steroid, flavonoid, and saponin. Ginger (Zingiber officinale Rosc.) also contains active components such as gingerol, paradol, and shogaol. These components in ginger and yellow melinjo peels are reported to have the activity to inhibit α-glucosidase. This research aim was to utilize yellow melinjo peel extract and ginger steep as functional drink that might have the activity to inhibit α-glucosidase. This research was divided into two stages. The preliminary stage was done to characterize yellow melinjo peel extract and ginger steep through activity inhibition of α-glucosidase, total phenolic, total flavonoid, and antioxidant activity. Main research was done to apply yellow melinjo peel extract and ginger steep into functional drink that use different concentration of yellow melinjo peel extract (0,12%, 0,16%, and 0,20%) and also using different concentration of stevia sweetener (0,3%; 0,4%; and 0,5%). All functional drinks’ formula was analyzed in organoleptic (scoring and hedonic), color, pH, and total soluble solids tests. The selected functional drink was analyzed for its activity of α-glucosidase inhibition, α-glucosidase inhibition kinetics, total phenolic, total flavonoid, and antioxidant activity. Yellow melinjo peel extract has activity inhibition of α-glucosidase (IC50)99.87 ppm, total phenolic 21.36 mg GAE/g, total flavonoid 11.97 mg QE/g, and antioxidant activity (IC50)1386.80 ppm. The ginger steep has activity inhibition of α-glucosidase (IC50)247811.5 ppm, total phenolic 0.29 mg GAE/g, total flavonoid 0.08 mg QE/g, and antioxidant activity IC50 60227.61 ppm. The selected functional drink from the hedonic test is the one with 0,20% extract and 0,5% stevia sweetener. The selected functional drink has inhibition of α-glucosidase IC50 194125 ppm, antioxidant activity (IC50)55497.12 ppm, total phenolic 0.64 mg GAE/mL, and total flavonoid 0.21 mg QE/mL.